Mapping Digital Asset Regulatory Models and Their Implications for Islamic Financial Governance: A Comparative Study of Indonesia, the United Arab Emirates, and Turkey - Rommy Hardyansah; Didit Darmawan (JURNAL AKTA, 2026)
This literature study conducts a comparative analysis of regulatory approaches to crypto assets and Central Bank Digital Currencies (CBDCs) within Islamic financial systems in Indonesia, the United Arab Emirates (UAE), and Turkey. Employing a qualitative normative juridical analysis method, the research examines secondary data from laws, financial authority regulations, and academic literature. The findings identify three distinct regulatory governance models: Indonesia's Dual-Track with Consolidated Market Governance model, which separates monetary authority for CBDCs from market oversight for crypto commodities and establishes a Self-Regulatory Organization (SRO); the UAE's Bank-Centric Integration with Centralized Licensing model, actively incorporating digital assets into the traditional banking supervisory framework; and Turkey's Payment Restriction with Supervised Trading model, prohibiting crypto for payments while permitting regulated exchange trading, with a cautious, phased CBDC development. The study reveals varied mechanisms for integrating Shariah principles, from structured compliance standards in exchanges to facilitating halal product innovation within integrated banking ecosystems and emphasizing macroeconomic prudence as a form of wealth protection (hifz al-mal). The research concludes that while convergence exists on goals of stability, consumer protection, and Anti-Money Laundering/Combating the Financing of Terrorism (AML/CFT), the divergence in integration levels and regulatory philosophy significantly shapes the future trajectory of modern, inclusive, and integrity-driven Islamic financial systems in the digital age. These models offer valuable policy pathways for other Muslim-majority jurisdictions navigating the complex intersection of financial technology innovation and Shariah compliance.